CITRA MANUSIA DARI FILSAFAT PSIKOLOGI KE FILSAFAT ANTROPOLOGI - Suhermanto Ja'far (Psympathic : Jurnal Ilmiah Psikologi, 2010)
According to existentialism and Iqbal, this writing is focused on human image. Human image (personality or ego) is as a charity. Iqbal’s philosophy of anthropology related to human concept and it focused on ego that is known as khudi.  According to Iqbal,  human ego is top of human perfection . He says also life is individual. So that, Iqbal gives the concept that human is as Khudi in which the human condition is difficult to definite because of the differences one each others.